2019
DOI: 10.1158/1538-7445.am2019-4140
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4140: Discovery and characterization of novel highly potent A2A adenosine receptor antagonists for cancerimmunotherapy

Abstract: Introduction: Extracellular adenosine produced at high concentrations within the tumor micro-environment (TME) and suppresses immune function via inhibition of immune cell activation. Targeting adenosine receptors has emerged as a novel method to activate anti-tumor immunity. In particular, A2A adenosine receptor (A2AR), one of the G-protein-coupled-receptors, exhibits immunosuppressive functions. Herein, we suggest novel A2AR antagonist lead compounds as a highly potent antagonist of A2AR for immunotherapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Accordingly, Hanmi Pharmaceutical may have selected a candidate and started a GLP (good laboratory practice) toxicity study in the second half of 2019. 124 3.2.6. iTeos. In preliminary studies, a research group from iTeos Therapeutics found that some of the A 2A R antagonists designed for Parkinson's disease dramatically lost potency in the high adenosine environment within tumors.…”
Section: Oncoimmunological Effects and Binding Modes Of Previouslymentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, Hanmi Pharmaceutical may have selected a candidate and started a GLP (good laboratory practice) toxicity study in the second half of 2019. 124 3.2.6. iTeos. In preliminary studies, a research group from iTeos Therapeutics found that some of the A 2A R antagonists designed for Parkinson's disease dramatically lost potency in the high adenosine environment within tumors.…”
Section: Oncoimmunological Effects and Binding Modes Of Previouslymentioning
confidence: 99%
“…significantly inhibited tumor growth in combination with anti-PD-L1 (10 mg/kg, iv, q3d). Accordingly, Hanmi Pharmaceutical may have selected a candidate and started a GLP (good laboratory practice) toxicity study in the second half of 2019 …”
Section: Small-molecule A2ar Antagonists For Cancer Immunotherapymentioning
confidence: 99%